The Predictive Roles Of Leadership And Communicating Religious Commitment In Energy Sustainability Change Readiness - Hana Panggabean; Juliana Murniati; Ratri Atmoko Benedictus; Rustono Farady Marta; Helmi Azahari (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2023)
Industrial fields of Indonesia are facing challenging issues of energy sustainability. As the country’s second-largest energy consumer behind the transportation sector, industrial’s consumption is massively dominated by non-renewable energy and the lack of adequate energy waste management. Organizations need to build employee readiness to change toward energy sustainability. Leadership is reasonably a significant predictor of organizational change readiness (RtC). Religious commitment (RC) emerges as a personal motivator for pro-environmental behaviour because individuals perceive looking after nature and the environment as adhering to religious values and teachings. The society of Indonesia views religiosity as a virtue and values social hierarchy as one of the most substantial social structures. Accordingly, this study aims to examine the predictive roles of leadership and RC on organizational RtC and the features in communicating both predictors in change leadership. A mix-method approach was carried out by delivering questionnaires (N=257), conducting interviews, and focus group discussions with 35 managers and employees in the textile industry. A significant influence of leadership on RtC is found, strengthened by the impact of RC. Qualitative findings depicted religious meanings of energy sustainability and how leaders communicate their religiosity in employee behavioral changes.